2021
DOI: 10.1111/andr.13105
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy modulation alleviates cryoinjury in murine spermatogonial stem cell cryopreservation

Abstract: Background: Cryopreservation can expand the usefulness of spermatogonial stem cells (SSCs) in various fields. However, previous investigations that have attempted to modulate cryoinjury-induced mechanisms to increase cryoprotective efficiency have mainly focused on apoptosis and necrosis.Objectives: This study aimed to establish an effective molecular-based cryoprotectant for SSC cryopreservation via autophagy modulation. Materials and methods:To determine the efficacy of autophagy modulation, we assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…PTL and 3-MA were dissolved in DMSO and NAC was dissolved in the basal medium to reach the following desired final concentrations: PTL (1 μM), 3-MA (0.1 μM), and NAC (1 mM). The concentration range of the inhibitors was based on previous studies ( Li-Weber et al, 2005 ; Xiao et al, 2016 ; Jung et al, 2022 ; Kim et al, 2024 ). To address potential antagonism when combining the inhibitors, concentrations were set lower than those typically used individually.…”
Section: Methodsmentioning
confidence: 99%
“…PTL and 3-MA were dissolved in DMSO and NAC was dissolved in the basal medium to reach the following desired final concentrations: PTL (1 μM), 3-MA (0.1 μM), and NAC (1 mM). The concentration range of the inhibitors was based on previous studies ( Li-Weber et al, 2005 ; Xiao et al, 2016 ; Jung et al, 2022 ; Kim et al, 2024 ). To address potential antagonism when combining the inhibitors, concentrations were set lower than those typically used individually.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy typically serves a protective role, acting as a dynamic circulatory system to mitigate cellular damage and maintain in vivo homeostasis [ 82 ]. In cancer, autophagy plays a crucial role in sustaining cancer cells during adverse conditions such as starvation, hypoxia, fozen and chemotherapy/radiotherapy [ 83 , 84 ]. This process offers protection against cell death and promotes cancer cell growth.…”
Section: Molecular Regulatory Mechanisms Of Tumor Dormancymentioning
confidence: 99%
“…In a similar vein, Gao et al [ 55 ] demonstrated that inhibiting autophagy triggered intrinsic apoptosis in immature oocytes during the vitrification-warming process, while Bang et al [ 56 ] depicted autophagic activation as a natural adaptive response to cold stress in vitrified-warmed oocytes. Conversely, Jung et al [ 9 ] suggested that autophagy could contribute to cryoinjury during SSC cryopreservation, indicating that excessive autophagy could result in cell death after freeze-thawing.…”
Section: Cryoinjury-induced Cell Death In Germ Cell Freezingmentioning
confidence: 99%
“…As such, the necroptosis inhibitor necrostatin-1 has shown beneficial effects on the proliferation rate while reducing necroptosis and apoptosis after thawing in SSC cryopreservation; it exerts these impacts by reducing ROS generation, apoptosis, and RIP1 activity [ 10 ]. The addition of pifithrin µ (a p53 inhibitor) or 3-methyladenine, which blocks autophagosome formation by inhibiting type III phosphatidylinositol 3-kinase, has been found to enhance cryoprotective effects and help maintain normal stem cell characteristics after thawing during SSC freezing [ 9 ]. Mitophagy, a selective autophagy that removes aged and damaged mitochondria, is also activated in frozen oocytes to improve survival by eliminating damaged mitochondria [ 55 ].…”
Section: New Strategies For Germ Cell Freezingmentioning
confidence: 99%
See 1 more Smart Citation